Home Voters, House Prices, and the Political Economy of Zoning - Kristof Dascher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
One explanation of the recent real estate bubble might point to homeowners' artificially restricting housing supply. While empirical work has not found unequivocal evidence in support of this hypothesis, homeowners may well be restricting supply nonetheless, and without this restriction manifesting itself in a simple – or even partial – positive correlation between homeownership and rent. Three points emphasized in this paper's model cloud the relationship between homeownership and rent observed in the data. First, rent rises diffuse across cities. Second, homeowners may only wish to impose restrictions to supply if tenants are not few. And third, homeowners may negotiate supply restrictions in neighboring tenant-dominated cities, giving rise to homeowner-tenant coalitions in non-obvious ways. – The paper's empirical part tests the model against a data set that combines micro data on homeowners and rents with information on East Germany's large scale demolition, with this demolition interpreted as one striking instance of zoning.
Keywords: R31; H73; D72; 330